Visionary Expectations and Novice Designers – Prototyping in Design Education - Schaeffer, Jennie Andersson; Palmgren, Marianne (Design and Technology Education: An International Journal, 2017)
In information design education, we strive to find methods that provide students with opportunities to explore different ways of learning and designing. We seek to support development of contextual competences that will be helpful in navigating an unknown future of design in society. A challenge in today’s design education is to formulate and use methods that support design students in developing competencies in the space between basic form training and context-rich training. The aim of this study was to evaluate prototyping exercises in design education where the focus was in that in-between space. The study is based on 33 prototyping workshops done between 2008 and 2015 and involving 160 students and two design teachers. Four different approaches to prototyping exercises are described, examined and evaluated: spatial prototyping: multi-material prototyping, physical prototyping and a mix between the latter two. physical multi-material prototyping. The results show that the prototyping exercises did support the learning of diverse competencies in the in-between space of basic form training and context training. However, the exercises were also counterproductive and met with different kinds of resistance. The results of the study invite to a dialogue on how different prototyping techniques can stimulate learning in relation to future design competences.